Effectiveness of using active drains in primary breast augmentation - Pidchenko , Yurii; Khrapach , Vasyl; Oleksandr, Khrapach (The Ukrainian Scientific Medical Youth Journal, 2024)
the purpose of this work was to analyze the etiopathogenetic hematoma risk factors in order to identify them at the stage of planning the operation. The risk of hematoma is directly dependent on the level of bleeding during the operation and the reliability of intraoperative hemostasis. In general, these factors affect the level of bleeding, shifting the coagulation balance towards hypocoagulation. In addition, they could increase blood pressure or the permeability of the vascular wall. Their knowledge and detection before surgery prevents the occurrence of potential complications and makes it possible to optimize the aesthetic result. In addition, the risk of postoperative hematoma may increase as the volume of surgery increases. This happens because of the gradual fatigue increase of the surgeon, as well as the development of systemic changes in the patient's body. A critical period was determined like 24 hours after surgery, when there is the highest risk of early complications. This period requires a careful approach in the postoperative care planning. The development of postoperative hematoma is associated with a number of negative consequences. Among them, the necessity of re-hospitalization and return to the operating room in order to achieve final hemostasis, loss of time for the surgeon, additional anesthesia for the patient, extended hospital stay and all associated financial losses. The development of a hematoma remotely increase the risk of capsular contracture, which is the one of the most common reasons for reoperations after breast augmentation and leads to significant stigmatization of female patients. The analysis of actual sources did not reveal the evident connection between the use of active drainage after primary breast augmentation and the prevention of early postoperative complications. Therefore, when comparing the positive and negative consequences of their routine use, according to current research, the negative ones prevail. The combination of such factors as the achievement of thorough intraoperative hemostasis, fixation of the mammary glands, and the use of properly selected compression underwear, makes it possible to abandon the routine use of active drains without increasing the risk of early complications development during primary breast augmentation. Considering the fact that the hematoma is a proven risk factor for the capsular contracture formation, it is necessary to further investigation of drains effectiveness in order to prevent the development of capsular contracture in the long term.